Hipotesis dan Variabel Penelitian: Tinjauan Konseptual dalam Metodologi Riset Pendidikan - Wanto Hermawan; Tesa Rama Primadona; Rika Sa`diyah (CV Global Research Publication, 2025)
This article aims to examine the fundamental concepts of hypotheses and variables in educational research methodology through a library research approach. Variables are understood as constructs that represent the educational phenomena under investigation, while hypotheses are provisional assumptions formulated based on logical relationships among variables. This study focuses on the discussion of conceptual definitions, characteristics, classifications, and functions of variables and hypotheses in developing a systematic research framework. The findings indicate that clarity in constructing variables and formulating theory-based hypotheses is an essential prerequisite for the coherence of educational research design. This article makes a conceptual contribution as a methodological reference for educational researchers, particularly novice researchers, in developing theoretical foundations and research designs in a more logical, directed, and scientific manner. The study also emphasizes that clarity in the relationships among variables and precision in hypothesis formulation directly influence the selection of research methods and data analysis, thereby enabling educational research to be designed in a more valid and systematic way.